Age and gender‐related differences in emotional and behavioural problems and autistic features in children and adolescents with Down syndrome: a survey‐based study of 674 individuals. Issue 6 (13th November 2016) - Nærland, T.; Bakke, K. A.; Storvik, S.; Warner, G.; Howlin, P.
Abstract: Background: Recent studies have indicated an increased risk of autism, behavioural and emotional problems and attention‐deficit/hyperactivity disorder in individuals with Down syndrome. Method: In a large‐scale survey‐based study, we examined the rates of these problems and their relationship to age and gender, in a sample of 674 individuals (4–18 years) with Down syndrome. The relationship with IQ level was also explored in a subsample ( n = 175). The Strengths and Difficulties Questionnaire and the Social Communication Questionnaire were used to assess behavioural and emotional problems and autism traits. Results: On the Strengths and Difficulties Questionnaire, peer problems were the most frequently reported difficulty (48% > cut‐off), followed by hyperactivity/inattention (34% > cut‐off). On the Social Communication Questionnaire, 37% scored at or above cut‐off (≥15) for autism spectrum disorder; 17% were at or above the suggested cut‐off (≥22) for autism. Little association between age and behavioural or emotional problems or with severity of autistic symptomatology was found. However, peer problems were more common in adolescents than in junior school children ( P < 0.001); Hyperactivity/inattention was less prevalent among adolescents ( P < 0.001). Conclusions: High rates of autistic features, emotional and behavioural problems are documented. These problems are related to age, gender and degree of intellectual disability.